EVALUASI PENENTUAN PERSONIL IT INFRASTRUKTUR PADA TNI AL MENGGUNAKAN KOMBINASI METODE AHP DAN VIKOR - Abdillah, Abdillah Imam Julianto; H.A Danang Rimbawa; Yudistira Asnar (Antivirus : Jurnal Ilmiah Teknik Informatika, 2023)
In the current development of technology, information technology is not only used in the economic field, but is divided into various fields, including the military world of the Navy. In order to promote the capability of human resources in the field of IT infrastructure in the Navy, it is necessary to select the right personnel in the maintenance of IT infrastructure assets, so as to obtain competent personnel output in answering future challenges. To facilitate the determination of the right IT infrastructure personnel, the author implements a system by combining the AHP and Vikor methods based on Python. The AHP method is used to determine the weight of criteria in the selection of IT personnel, and the Vikor method is used to rank the appropriate IT personnel. With this system, it is hoped that it can be a supporting application to help select IT personnel according to tactical, technical, strategic criteria.